Efeitos do metacaulim sobre blocos intertravados de concreto (pavers). - Estolano, Amanda Marques Lopes (2018)
The effects of the metakaolin on the mechanical properties of the of compressive strength and abrasion of concrete interlocking blocks, as well as on the processing steps were evaluated. The pavers were carried out with 0%, 10%, 15%, 20%, 25% and 30% metakaolin additions. All these materials were fabricated by employing the following precursors: 50 kg of Portland cement type II; 50 kg of gravel; 80 kg of stone powder; 140 kg of sand; and 15 L of water, whose water cement ratio was 0.3. In addition, the mechanical properties revealed that all metakaolin pavers presented larger values of compressive strength (~ 37 MPa) when compared to the corresponding value of the blocks with absence of metakaolin (~30 MPa), i.e., the metakaolin addition enhanced the compressive strength property in 24%. Although the contents with 20%, 25% and 30% of addition, this property did not show significant variation. Further, a chemical rationalization of the steps associated with the fabrication of the concrete pavers was carried out. The results indicated that for the metakaolin pavers with 30% addition of the metakaolin, the water quantity is not capable to transform both calcium oxide and aluminum oxide in their corresponding hydroxide compounds in an efficient manner. These experiments by fluorescence microscopy indicated that the metakaolin addition of 10% presented a high yield as regards the hydration reactions of the cement. Furthermore, for the other cases the anhydrous cement was left over. This is evidenced by the exacerbated fluorescence in the blue region. On the other hand, it was also evaluated in this work, the usage of the metakaolin as a partial substitute for the Portland cement. The results showed that the concrete blocks with absence of the metakaolin had the largest values of compressive strength when compared to the cases where the cement was replaced by metakaolin. Finally, when it was evaluated all different types of concrete studied in this work, the metakaolin addition of 10% in the precursor mixture leads to the concrete with larger potentiality for applications in civil constructions.